Analisis Kemampuan Menulis Teks Eksposisi melalui Metode Berbasis Praktik Kelas VIII SMP Swasta Cenderamata - Nurhasanah Nurhasanah; Panigoran Siburian; Wahyu Ningsih (YASIN, 2026)
This study was motivated by the low ability of eighth-grade students at SMP Swasta Cenderamata to write expository texts, particularly in understanding text structure, developing logical arguments, and using effective language. This study aimed to analyze students’ expository text writing ability through the implementation of a practice-based learning method. The study employed a descriptive qualitative approach with a field research design, involving all eighth-grade students at SMP Swasta Cenderamata as participants. Data were collected through observations of the learning process, interviews with teachers and students, and documentation of students’ written work, and were analyzed using an interactive analysis model consisting of data reduction, data display, and conclusion drawing. The findings show that implementing a practice-based learning method significantly improved students’ expository text writing ability, as reflected in their progress in formulating a thesis, developing arguments, and writing reiteration in accordance with the structure of expository texts. In addition, students’ engagement and motivation in writing instruction increased because they were directly involved in each stage of the writing process, from planning to revision. Nevertheless, several challenges remained, including limited vocabulary, difficulties in developing ideas in depth, and mechanical errors in writing. This study concludes that a practice-based learning method is effective and relevant for improving students’ expository text writing skills, and it underscores the importance of practice-oriented writing instruction to enhance the quality of Indonesian language learning processes and outcomes.